Perencanaan Strategis Teknologi Informasi Terhadap Perusahaan Menggunakan Pendekatan Ward and Peppard - Rizqi Falih Hamidan; Oky Irnawati (Jurnal Manajemen Informatika JAMIKA, 2023)
Strategic planning in information technology is a planning activity carried out by utilizing technology optimally to support the company's business objectives. This strategic planning must consider the continuous development of information technology to maintain the competitive advantage of a company. The research objective is to analyze the company's internal and external conditions to determine the strengths, weaknesses, opportunities and threats to CV. Medica Trisari which is useful for making strategic planning for information systems. The data collection method used in the research to be carried out uses the Observation, Interview, and Literature Study methods. Then use the SWOT Analysis method which can analyze the strengths, weaknesses, opportunities and threats that exist within the Company using the Ward and Peppard approach to ensure IS/IT strategic planning. From the results of the SWOT analysis, several strategic plans were obtained for CV Medica Trisari in developing IS/IT management so that it is able to compete with other competitors. Thus, it can be concluded that the CV. Medica Trisari Company strategy shows a good graph and has a quadrant 1 value. By using McFarlan Strategic Grid analysis, IS/IT output is produced which is expected to be a solution to business process problems and improve the quality of company management.